Algivory in hawksbill turtles: Eretmochelys imbricata food selection within a foraging area on the Northern Great Barrier Reef. (27th June 2012) - Bell, Ian
Abstract This paper describes the food selection of hawksbill turtles, Eretmochelys imbricata, using reefs of the Far Northern Section of the Great Barrier Reef Marine Park (nGBR) during 2006 and 2007. A total of 467 gastric lavage and 71 buccal cavity ingesta items were collected from 120 individual E. imbricata, comprising adult female and immature turtles of both sexes. Nineteen E. imbricata that were captured in 2006 were recaptured and sampled again in 2007. Within the total pooled buccal and lavage sample (n = 538), the occurrence of food items was dominated (72.7%) by only three algal taxonomic divisions: Rhodophyta (red algae; 53.7%, n = 289); Chlorophyta (green algae; 11.0%, n = 59) and algae from the division of Phaeophyceae (brown algae; 8.0%, n = 43). The remaining total (buccal and lavage) ingesta sample comprised sponges (10.4%, n = 56), soft corals and a wide variety of possibly nutritionally important invertebrate species (12.6%, n = 68), and a small percentage (5.4%, n = 22) of inorganic material. Generally, E. imbricata were considered to be primarily a sponge‐feeding specialist and secondarily an omnivorous species; within coral reef habitats and in various parts of the world this is the case. However, this study has shown that E. imbricata found foraging on reefs of the nGBR are primarily algivorous and secondarily omnivorous. A feeding strategy that relies on a predominantly algal diet may infer important benefits to the species if the impacts of climate change and ocean acidification inhibit coral growth, while promoting algal density and distribution within the Great Barrier Reef ecosystem.